2016
DOI: 10.1089/jpm.2015.0464
|View full text |Cite
|
Sign up to set email alerts
|

The Spectrum of Caregiving in Palliative Care for Serious, Advanced, Rare Diseases: Key Issues and Research Directions

Abstract: Rare diseases are often life-limiting conditions, the majority of which require constant caregiving needs. The realization of a spectrum of palliative care throughout the trajectory of rare diseases could ensure individualized and caregiver-focused approaches to the care of patients and families. In June 2015, the National Institute of Nursing Research (NINR), the lead institute at the National Institutes of Health for end-of-life research, in conjunction with the National Center for Advancing Translational Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 38 publications
(52 reference statements)
0
13
0
Order By: Relevance
“…43,67 Finally, models for addressing social support needs alongside illness-directed care, a major need identified by the Institute of Medicine, are needed. 12 Elucidating the impact of simultaneous stressors 10,67,68 and potential stress-buffering resources 69,70 can inform services geared toward particular family strengths and demands.…”
Section: Discussionmentioning
confidence: 99%
“…43,67 Finally, models for addressing social support needs alongside illness-directed care, a major need identified by the Institute of Medicine, are needed. 12 Elucidating the impact of simultaneous stressors 10,67,68 and potential stress-buffering resources 69,70 can inform services geared toward particular family strengths and demands.…”
Section: Discussionmentioning
confidence: 99%
“…The US National Institutes of Nursing Research does a lot of research on end-of-life issues and have identified the following research gaps: living with uncertainty; the costs of caregiving; communication; interventions for ethnically and culturally diverse populations; and transitions in care. 214,215 We have much to learn from our patients 216,217 and our European colleagues 218 in this area. Although some foundations fund end-of-life research, 219 overall federal funding for end-of-life research is small and should be expanded.…”
Section: Supportive Carementioning
confidence: 98%
“…16 The required multidisciplinary care is often uncoordinated, placing an additional burden on the patient. 3,4,17 A key challenge preventing RDs from being adequately addressed in LMIC is the slow development of RD diagnosis and research in the context of global collaboration. 16 The paucity of characterized local genetic variants and the often complex relationship between phenotype and genotype require attention in these LMIC.…”
Section: Impact Of Rds On Childrenmentioning
confidence: 99%